Lawmaking - White, Nigel D. (Oxford University Press, 2016)
Virtually every important question of public policy today involves an international organization. From trade to intellectual property to health policy and beyond, governments interact with international organizations in almost everything they do. Increasingly, individual citizens are directly affected by the work of international organizations.